The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cctc.202201174
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Buffer, Pyridoxal 5’‐Phosphate and Light on the Stability of the Silicibacter Pomeroyi Transaminase

Abstract: Transaminases are pyridoxal 5'-phosphate (PLP)-dependent enzymes that transfer amino-functions. The transaminase from Silicibacter pomeroyi (SpATA) exhibits a broad substrate spectrum. In this work we examined the effect of different conditions (light, buffer and PLP-concentration) on the stability of SpATA, as well as the causes for these effects. The enzyme was stored either in TRIS or CHES with 0-10 mM added PLP at 22 °C. The samples were either kept dark or they were exposed to light. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/catal13020300/s1. Section S1: establishment of optimal immobilization conditions for each transaminase; Figure S1: establishment of optimal immobilization conditions Table S1: optimal immobilization conditions for each transaminase; immobilization parameters; Table S2: immobilization parameters; Section S2: methods and additional data on transaminase stability and activity; general setup of sample incubation [7,8,63,91,92]; Figure S2: stability and reactivity of ATA-Vfl, ATA-3FCR-5M, and ATA-Lsy under different conditions; Section S3: post-cross-linking and storage of dried beads; Figure S3: effect of post-cross-linking on specific activity of the immobilizates; Figure S4: effect of drying on specific activity of the immobilizates; Section S4: upscaled kinetic resolution catalyzed by the final immobilizates; Figure S5: chiral HPLC runs; Figure S6: exemplary NMR analysis of (S)-1-PEA. ; Figure S7: behavior of acetophenone and 1-phenylethylamine in bead-containing solutions; Section S5: cloning of transaminases; Table S3: components and concentrations of the add-on and OE-PCR [46]; Table S4: PCR program for the add-on and OE-PCRs; Section S6: nucleic acid sequences; open reading frames of ATA-Bmu, ATA-3FCR-5M, and ATA-Lsy in respective plasmids w/o aldehyde-tag; open reading frames of ATA-Bmu, ATA-3FCR-5M, and…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/catal13020300/s1. Section S1: establishment of optimal immobilization conditions for each transaminase; Figure S1: establishment of optimal immobilization conditions Table S1: optimal immobilization conditions for each transaminase; immobilization parameters; Table S2: immobilization parameters; Section S2: methods and additional data on transaminase stability and activity; general setup of sample incubation [7,8,63,91,92]; Figure S2: stability and reactivity of ATA-Vfl, ATA-3FCR-5M, and ATA-Lsy under different conditions; Section S3: post-cross-linking and storage of dried beads; Figure S3: effect of post-cross-linking on specific activity of the immobilizates; Figure S4: effect of drying on specific activity of the immobilizates; Section S4: upscaled kinetic resolution catalyzed by the final immobilizates; Figure S5: chiral HPLC runs; Figure S6: exemplary NMR analysis of (S)-1-PEA. ; Figure S7: behavior of acetophenone and 1-phenylethylamine in bead-containing solutions; Section S5: cloning of transaminases; Table S3: components and concentrations of the add-on and OE-PCR [46]; Table S4: PCR program for the add-on and OE-PCRs; Section S6: nucleic acid sequences; open reading frames of ATA-Bmu, ATA-3FCR-5M, and ATA-Lsy in respective plasmids w/o aldehyde-tag; open reading frames of ATA-Bmu, ATA-3FCR-5M, and…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…4 min in a reactor volume of 236 µL (Figure 3). The column and feed solution were kept dark to avoid the inactivating effect of light on ATA-Spo [49,50]. The protein concentration in the flow-through was analyzed with the Bradford Assay, but no detectable enzyme leaching was observed.…”
Section: Amination Of Hmf In Continuous Flow Using Immobilized Ata-sp...mentioning
confidence: 99%
“…The feed solution (50 mM HEPES buffer pH 8.0, 10 mM HMF, 0.1 mM PLP, and 500 mM amine donor (isopropylamine or L-alanine)) was pumped through the tube with a flow rate of 50 µL min −1 . The tube and the feed solution were wrapped in aluminum foil to exclude negative influences from light [49,50]. Samples of the flow were taken every 24 h and analyzed using HPLC.…”
Section: Continuous Flow Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme was previously shown to be active on oxidized mono- and oligosaccharide substrates [ 13 ], however, its activity towards higher molecular weight oxidized polysaccharides is unknown. Previous studies showed that SpATA can accept bulky substrates including Jeffamines and halogenated prochiral ketones [ 25 , 26 ], which makes it a promising enzyme for polysaccharide amination. In this study, a new colorimetric assay was established to compare the yield of aminated polysaccharides produced by CvATA and SpATA.…”
Section: Introductionmentioning
confidence: 99%